Question

\[ f(x) = 3x + 4 \quad g(x) = 2x - 3 \] \[ \text{Tìm: } f \circ g(x) \]

Ask by Cruz Paul. in Vietnam
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( f \circ g(x) = 6x - 5 \)

Solution

Để tìm hàm hợp \( f \circ g(x) \), chúng ta thực hiện như sau: \[ f \circ g(x) = f(g(x)) \] Với các hàm đã cho: \[ f(x) = 3x + 4 \] \[ g(x) = 2x - 3 \] Thay \( g(x) \) vào hàm \( f \): \[ f(g(x)) = f(2x - 3) = 3(2x - 3) + 4 \] Tiến hành tính toán: \[ 3(2x - 3) + 4 = 6x - 9 + 4 = 6x - 5 \] Vậy: \[ f \circ g(x) = 6x - 5 \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

Để tìm \( f \circ g(x) \), chúng ta sẽ thay giá trị của \( g(x) \) vào hàm \( f(x) \). Bước đầu tiên là tìm \( g(x) \): \[ g(x) = 2x - 3 \] Tiếp theo, thay \( g(x) \) vào \( f(x) \): \[ f(g(x)) = f(2x - 3) = 3(2x - 3) + 4 \] Bây giờ, chúng ta thực hiện các phép toán: \[ = 6x - 9 + 4 \] \[ = 6x - 5 \] Vậy, \( f \circ g(x) = 6x - 5 \).

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy